2019
DOI: 10.1016/j.cell.2019.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Structural Mechanism of EMRE-Dependent Gating of the Human Mitochondrial Calcium Uniporter

Abstract: Mitochondrial calcium uptake is crucial to the regulation of eukaryotic Ca 2+ homeostasis and is mediated by the mitochondrial calcium uniporter (MCU). While MCU alone can transport Ca 2+ in primitive eukaryotes, metazoans require an essential single membrane-spanning auxiliary component called EMRE to form functional channels; however, the molecular mechanism of EMRE regulation remains elusive. Here, we present the cryo-EM structure of the human MCU-EMRE complex, which defines the interactions between MCU and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
237
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(258 citation statements)
references
References 58 publications
19
237
2
Order By: Relevance
“…Here, we perform the most comprehensive phylogenomic analysis of the mt-Ca 2+ uptake system and trace its evolution across 1,156 fully-sequenced eukaryotes. In contrast to earlier assumptions 911 we find compelling evidence that previously identified animal and fungal MCUs, the targets of several structural and functional efforts 1116 , represent two distinct paralogous subfamilies originating from an ancestral duplication. We further uncover a complete “animal-like” uniporter complex within chytrid fungi, including bona-fide orthologs of MCU, MICU1, and EMRE.…”
contrasting
confidence: 77%
See 2 more Smart Citations
“…Here, we perform the most comprehensive phylogenomic analysis of the mt-Ca 2+ uptake system and trace its evolution across 1,156 fully-sequenced eukaryotes. In contrast to earlier assumptions 911 we find compelling evidence that previously identified animal and fungal MCUs, the targets of several structural and functional efforts 1116 , represent two distinct paralogous subfamilies originating from an ancestral duplication. We further uncover a complete “animal-like” uniporter complex within chytrid fungi, including bona-fide orthologs of MCU, MICU1, and EMRE.…”
contrasting
confidence: 77%
“…Instead, EMRE was found as a specific interactor of MCU in human cells, required for both conductivity and binding of the channel to MICU1 8 . Although MCU and MICU1 showed correlated evolutionary histories across 138 sequenced eukaryotic organisms, EMRE apparently lacked any homolog outside the metazoan lineage and it was therefore suggested to be an animal-specific innovation 911 . While those observations pointed to an ancient eukaryotic origin of mt-Ca 2+ uptake, they also implied a very different composition and regulation of the uniporter in different clades.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Such polar interactions are also observed in the crystal structures of the HsMCU-NTD. Apart from the interfaces within one MCU channel, extensive dimerization interactions at the NTD were observed in the cryo-EM structure of MCU-EMRE complex that multiple sets of salt bridges and hydrogen bonds forms the dimerization interface between two MCU tetramers (Wang et al, 2019). In DdMCU-NTD crystal structures, three pairs of parallel polar interactions are also identified, including N59/D60-N93, K66-D74, E72-N76, which play an important role in the formation and stabilization of the DdMCU-NTD oligomers.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, the NTDs of these homologues also share high structural similarity despite of the low sequence homology between NTDs. Recently, Wang et al reported the cryo-EM structure of the human MCU-EMRE complex, providing the structural features for the EMRE regulation on the conformation of HsMCU (Wang et al, 2019). It is interesting to note that the NTD adopts a unique side-by-side configuration to mediate the dimerization of two HsMCU tetramers, which indicates that the NTD may play an important role in modulating the function of MCU, although the removal of the NTD does not affect mitochondrial Ca 2+ uptake (Lee et al, 2015).…”
mentioning
confidence: 99%